Islam dan Demokrasi di Indonesia: Dialektika Agama, Kekuasaan dan Persoalan Moderasi BeragamaIslam dan Demokrasi di Indonesia: Dialektika Agama, Kekuasaan dan Persoalan Moderasi Beragama - Satryo Pringgo Sejati; Ahmad Burhan Hakim (JOSH: Journal of Sharia, 2026)
Democracy in Indonesia is the result of a complex and dynamic interaction between Islamic values ​​and political practices evolving within society. This process not only creates synergy between Islamic principles and democratic values ​​but also strengthens the government's legitimacy and creates space for more inclusive public participation. In this context, Islam serves not only as a belief system but also as a moral foundation that can support just and democratic political practices. The relationship between Islam and democracy in Indonesia demonstrates that religious values ​​can contribute significantly to social and political stability, creating a harmonious and inclusive society. The importance of dialogue between political leaders and the Islamic community is crucial in identifying challenges faced in realizing a more inclusive democracy. This study aims to explore how Islamic values ​​can reduce radicalism and support the strengthening of democracy in Indonesia. In this regard, religious moderation is key to creating constructive dialogue and reducing the potential for conflict, thus supporting a more stable democratic environment. Through an inclusive and collaborative approach, it is hoped that education that emphasizes the values ​​of religious moderation can shape a tolerant and diverse young generation, and encourage interfaith cooperation in a multicultural society. Thus, this research is expected to provide a significant contribution to the development of effective and sustainable religious moderation policies, as well as supporting social and political stability in Indonesia.